DETERMINATION OF MACRONUTRIENTS IN SPICES BY INDUCTIVELY COUPLED PLASMA-OPTICAL EMISSION SPECTROMETRY - Khan, Naeem; Choi, Ji Yeon; Nho, Eun Yeong; Habte, Girum; Jamila, Nargis; Hong, Joon Ho; Ryu, Keun Yeoung; Park, Kyung Su; Kim, Kyong Su (TAYLOR & FRANCIS INC, 2014)
The concentrations of the macronutrients sodium, potassium, calcium, magnesium, phosphorus, and iron were determined in spices by microwave-assisted digestion with nitric acid and hydrogen peroxide and analyzed by inductively coupled plasma-optical emission spectrometry (ICP-OES). The analytical methods were validated by recovery checks and the analysis of spinach leaves Standard Reference Material (NIST-1570a). The concentrations were dependent upon the identity of the spice. Potassium, calcium, and magnesium were the most abundant elements, followed by sodium, iron, and phosphorus. Concentrations of all analyzed elements were comparable to the published literature on spices and met the critical limits of Recommended Dietary Allowances and Tolerable Upper Levels, specified by the Food and Nutrition Board, USA.